Digital Media Communication Of Tribal Organizations As Public Policy Information Literacy Education In Langkat District - Indra, Farhan; P, Indira Fatra Deni; Sikumbang, Ahmad Tamrin; Sintya, Dina Ika; Fadli, Ajril; Lubis, Putri Rahmadhani (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this study is to determine how tribal organizations in the Langkat area use digital media to make public policy information more accessible. It also aims to identify the information that is disseminated and to analyze the barriers that stand in the way of these organizations using digital media. Four groups in Langkat Regency—DMDI (Dunia Melayu Dunia Islam), PMS (Pemuda Merga Silima), Puja Kesuma, and PBB (Pemuda Batak Bersatu)—served as the primary sources for this study. qualitative research methodology using focus group discussions and in-person informant interviews. Technological determination is the theory that guided this investigation. According to the study's findings, tribal organizations in Langkat Regency use social media and online news sources to disseminate information about their own organization's interests, security, and social order, as well as social, cultural, and health-related topics. The firm has never provided technical publication operators with training, thus the challenges they face are technological in nature.